Agriculture and the Clean Development Mechanism - Larson, Donald F.; Dinar, Ariel; Frisbie, J. Aapris (2012)
Many experts believe that low-cost mitigation opportunities in agriculture are abundant and comparable in scale to those found in the energy sector. They are mostly located in developing countries and have to do with how land is used. By investing in projects under the Clean Development Mechanism (CDM), countries can tap these opportunities to meet their own Kyoto Protocol obligations. The CDM has been successful in financing some types of agricultural projects, including projects that capture methane or use agricultural by-products as an energy source. But agricultural land-use projects are scarce under the CDM. This represents a missed opportunity to promote sustainable rural development since land-use projects that sequester carbon in soils can help reverse declining soil fertility, a root cause of stagnant agricultural productivity. This paper reviews the process leading to current CDM implementation rules and describes how the rules, in combination with challenging features of land-use projects, raise transaction costs and lower demand for land-use credits. Procedures by which developed countries assess their own mitigation performance are discussed as a way of redressing current constraints on CDM investments. Nevertheless, even with improvements to the CDM, an under-investment in agricultural land-use projects is likely, since there are hurdles to capturing associated ancillary benefits privately. Alternative approaches outside the CDM are discussed, including those that build on recent decisions taken by governments in Copenhagen and Cancun.